Comparison between FOUR score and GCS in assessing patients with traumatic head injury: a tertiary centre study - Nair, Sharath S.; Surendran, Anilkumar; Prabhakar, Rajmohan B.; Chisthi, Meer M. (International Surgery Journal, 2017)
Background: Head injuries are a major cause of mortality and morbidity across the world. Effective initial assessment and early intervention is of importance in patients with traumatic brain injury, so as to ensure the maximum favorable outcome. Glasgow Coma Scale is the widely accepted scale to assess severity in head injury patients, albeit with many inadequacies. The objective of this study was to test the validity of full outline of unresponsiveness score, an alternate tool, in assessing severity in patients with traumatic brain injury. Methods: This was a descriptive study, conducted on 69 patients admitted to the general surgical and neuro-surgical wards of Government Medical College, Trivandrum, India with traumatic head injury. For all these patients, full outline of unresponsiveness score and Glasgow Coma Scale were calculated at the time of presentation and serially thereafter. The predictive value of full outline of unresponsiveness score as well as its correlation with Glasgow Coma Scale was studied. Results: A statistically significant correlation was found between full outline of unresponsiveness score and Glasgow Coma Scale in estimating the severity of head injury. Also Full Outline of unresponsiveness score was able to furnish better details about the neurological status of trauma patients. Conclusions: As per the results, it can be concluded that the full outline of unresponsiveness score can be applied as an ideal tool to evaluate consciousness levels and patients’ status in patients with traumatic head injury. It can be used as the ideal replacement for Glasgow Coma Scale.